Perbandingan Efisiensi Teknik PWM dan VFD dalam Pengendalian Motor Listrik - Moh. Nizar Khamdun (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study discusses the comparison of efficiency between Pulse Width Modulation (PWM) and Variable Frequency Drive (VFD) techniques in electric motor control. The background of this research is based on the importance of energy efficiency in industrial applications using electric motors. The aim of this study is to identify the advantages and disadvantages of each method in the context of energy savings and motor performance. The method used is a quasi-experimental design, where both techniques are tested on the same three-phase induction motor to compare power consumption and operational efficiency. The findings indicate that the use of VFD is significantly more efficient in reducing power consumption compared to PWM and provides better torque stability in the motor. The implications of this research suggest that the application of VFD can enhance energy efficiency and reduce operational costs, which is crucial for industries. This study is expected to serve as a reference for further development in electric motor control technology.